Parental perceptions regarding the experiences of African American children in multiple settings (church & school) located within predominately white communities - Coleman, Kieran Dwayne, author; Foster, Ann M., advisor; Middleton, Vallarie, advisor; Cross, Jennifer E., committee member; Banning, James H., committee member (Colorado State University. Libraries, 2003)
Since the 1960's, there has been a growing number of African American/Black families who reside in predominately white communities. Interestingly enough, after forty years, there is still a small amount of research that focuses on middle class Black families, in comparison to at-risk studies on poor black families. In an effort to add to the research on middle class African American families, this study examines how parents of African American children perceive their children's experiences in two important settings- a multiracial church and predominately white public schools, found within predominately white communities where Blacks represent less than 2%. This qualitative study involved twelve in-depth interviews focusing on parental perceptions and their children's experiences in church and school settings located within predominately white communities. Five themes were identified in the study. Of the five themes, three themes focused on the school and its influence on the participants' children. These themes are (1) In case you didn't know, (2) It's the intent, and (3) At what cost? The other two themes, (4) The other school, and (5) We care, focused on the relationships and the impact the church had on these children. Findings in this study indicated the following: (1) a school choice policy played a unique role in helping parents find schools for their children that stressed academic success and cultural responsiveness; (2) a multiracial church played an important role in developing student identity and broadening cultural experiences, and (3) care plays an important role in the developmental stages of African American children. Suggestions and recommendations, included in this study, are provided for school districts, teachers and parents of African American children.
Keywords: bilingual education; multicultural education; minority and ethnic groups; sociology; ethnic studies